The Legacy of A.S. Neill in Finland - Sorainen, Antu (Revista Hipótese, 2018)
This article looks first briefly on the history of education and the influence of A.S. Neill’s ideas in Finland, and then turns into a roundtable where three people –two mothers and one son –discuss their own experiences of the Summerhillian kindergarten in Finland, and the future of alternative education in the era of neo-liberalism.